Online Exam Application Study Using the Pieces Framework Method - Freshtiya Beby Larasati; Lise Pujiastuti; Solikhun Solikhun (Jurnal Mantik, 2021)
To find out the level of success in web-based or online implementation and have to do an evaluation. Evaluation is in the form of a reference or benchmark used in relation to the audit of the information system analysis method itself, by looking at the performance of a system quantitatively and qualitatively. The purpose of this study was to evaluate the level of success, efficiency, effectiveness, and company profits in implementing an online-based exam system conducted at the AMIK Tunas Bangsa Pematangsiantar campus. In providing analysis or evaluation of a system, it can be done with several analytical models. In this study, a model analysis framework will be used, namely by using the Pieces Framework method.